2021
DOI: 10.1016/j.lungcan.2021.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Age disparities in lung cancer survival in New Zealand: The role of patient and clinical factors

Abstract: Age is an important prognostic factor for lung cancer. However, no studies have investigated the age difference in lung cancer survival per se. We, therefore, described the role of patient-related and clinical factors on the age pattern in lung cancer excess mortality hazard by stage at diagnosis in New Zealand. Materials and Methods: We extracted 22 487 new lung cancer cases aged 50-99 (median age = 71, 47.1 % females) diagnosed between 1 January 2006 and 31 July 2017 from the New Zealand population-based can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 37 publications
7
19
0
Order By: Relevance
“…Multivariable Cox regression analysis showed that seven clinical factors including age, gender, marital status, T stage, N stage, surgical type, and radiation were signi cantly associated with OS. Among them, patients aged >77 years presented a signi cantly higher risk of death than those aged <67, implying that age is a poor prognostic factor for lung squamous cell carcinoma, which is consistent with previous studies [29,30]. Many studies revealed sex differences existing in survival and female lung cancer patients have higher survival [31,32].…”
Section: Discussionsupporting
confidence: 86%
“…Multivariable Cox regression analysis showed that seven clinical factors including age, gender, marital status, T stage, N stage, surgical type, and radiation were signi cantly associated with OS. Among them, patients aged >77 years presented a signi cantly higher risk of death than those aged <67, implying that age is a poor prognostic factor for lung squamous cell carcinoma, which is consistent with previous studies [29,30]. Many studies revealed sex differences existing in survival and female lung cancer patients have higher survival [31,32].…”
Section: Discussionsupporting
confidence: 86%
“…Women’s median survival time and 3-year, 5-year, and 10-year survival rates were more significant and growing faster than men’s. Pilleron et al 18 also found that gender was one of the most important factors influencing lung cancer survival time. The prognosis of female patients undergoing lobectomy/segmentectomy was significantly better than in male patients.…”
Section: Discussionmentioning
confidence: 97%
“…Our results were highly consistent with previous results [ 15 ]. Previous research found that patients who were older at onset had more comorbidities, poorer performance status, lower tolerance of treatment and a worse prognosis [ 23 , 24 ]. Some studies have reported a worse prognosis in females than males [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%